An Experiment in the Study of Translations: Prismatic Jane Eyre [dataset] - Reynolds, M; Vitali, GP; Landucci, S (University of Oxford, 2024)
Charlotte Brontë’s Jane Eyre has been translated hundreds of times into more than 60 different languages. Each translation brings not only losses but also gains and transformations in understanding, expression, and political and imaginative energies. The Prismatic Jane Eyre project set out to discover how we can grasp the dizzying textual and linguistic proliferation of the text, and what we can learn by studying it. The header image shows various Jane Eyre book covers taken from editions of the novel printed around the globe. We believe that our representation of these book covers falls under the provision for fair use for the purposes of scholarship and education: if you are a copyright holder and would like to discuss this please contact the project via: https://prismaticjaneeyre.org/feedback/